2022
DOI: 10.1002/cam4.5555
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors associated with the prognosis of papillary thyroid cancer and the construction of a survival model

Abstract: Objective: To study the survival prediction value of lymph node ratio (LNR) and preoperative thyroglobulin (Tg) in the prognosis of thyroid papillary carcinoma (PTC).Methods: A total of 495 patients with PTC and lymph node metastasis treated at the Cancer Hospital of Xinjiang Medical University were selected for a retrospective study. The disease-free survival (DFS) of patients was the follow-up endpoint. DFS was calculated for all patients. The Cox proportional risk regression model and nomogram were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“… 10 Some other studies have reported analysis of the risk and prognosis of lymph node metastasis in thyroid cancer based on clinical features, but the supplementary performance of imaging features is lacking and needs to be further improved. 11 13 Current imaging methods for thyroid cancer lymph node metastasis have low diagnostic efficiency and exhibit significant variation. Therefore, we use PET/CT multi-modal imaging data and combine the advantages of radiomics to improve the diagnostic efficiency of lymph node metastasis.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Some other studies have reported analysis of the risk and prognosis of lymph node metastasis in thyroid cancer based on clinical features, but the supplementary performance of imaging features is lacking and needs to be further improved. 11 13 Current imaging methods for thyroid cancer lymph node metastasis have low diagnostic efficiency and exhibit significant variation. Therefore, we use PET/CT multi-modal imaging data and combine the advantages of radiomics to improve the diagnostic efficiency of lymph node metastasis.…”
Section: Introductionmentioning
confidence: 99%